1999
DOI: 10.1038/sj/leu/2401555
|View full text |Cite
|
Sign up to set email alerts
|

True

Abstract: Significance of commonly used prognostic factors differs for children with T cell acute lymphocytic leukemia (ALL), as compared to those with B-precursor ALL. A Pediatric Oncology Group (POG) studyT cell acute lymphocytic leukemia (T-ALL) and B-precursor ALL differ significantly in the clinical characteristics of the patients at presentation and in laboratory-defined characteristics of the leukemic cells. We assessed for pediatric patients with T-ALL the relative importance of prognostic factors previously dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…T-cell ALL patients may present with high WBC and yet may have acceptable OS [20]. The T-cell ALL group in our study was too small to analyze the relative importance of morphology and WBC count.…”
Section: Discussionmentioning
confidence: 97%
“…T-cell ALL patients may present with high WBC and yet may have acceptable OS [20]. The T-cell ALL group in our study was too small to analyze the relative importance of morphology and WBC count.…”
Section: Discussionmentioning
confidence: 97%
“…In the clinical setting, age and white blood cell count (WBC) at diagnosis are used to stratify B-lineage ALL patients as either standard or high risk, significantly impacting on the type and intensity of post-induction therapy used. However these NCI-defined criteria have been shown to have little prognostic value in T-ALL disease [1-3]. Improved markers are needed for outcome prediction to improve T-ALL patient stratification.…”
Section: Introductionmentioning
confidence: 99%
“…In the GMALL trial, presenting WBC did not reach statistical significance in multivariate analysis [7] while in the JALSG trial, patients with WBC <3 × 10 9 /l or >50 × 10 9 /l had a worse outcome than patients with a WBC of 3–50 × 10 9 /l [5]. The Pediatric Oncology Group study of pediatric T-ALL reported a similar trend as patients with WBC <10 × 10 9 /l or >50 × 10 9 /l did worse than patients with a WBC of 10–50 × 10 9 /l [20]. In our T-ALL cohort, initial WBC [analyzed as a continuous variable or categorically using 3, 10 and 50 as cutoffs according to previous reports (data not shown)] did not influence outcome.…”
Section: Discussionmentioning
confidence: 50%